1995
DOI: 10.1002/jsfa.2740670209
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical and nutritional changes in fish proteins during drying

Abstract: Biochemical and nutritional changes in the muscle proteins of a lean marine fish Nempiterus japonicus during drying at 50, 60 and 70°C were investigated. Solubility of proteins in water, 0.6 M NaCI, 1.5 M urea, 8 M urea and 10 g litre-* sodium dodecyl sulphate (SDS) decreased as drying progressed at all three temperatures; most of the decrease occurring in the initial 4 h of drying. SDS-polyacrylamide gel electrophoresis of 1.5 M urea, 8 M urea and SDS extracts showed that higher molecular weight (MW) protein … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 15 publications
1
8
0
Order By: Relevance
“…The retention of the nutritional value of food products is dependent mainly on the freshness of the raw material and optimal control of associated drying conditions [37]. The heat effects involve in drying affect the protein components in foods especially the thiosulphide groups [38]. Its causes changes in the solubility of proteins, hydrophobic bond break has been attributed greatly to denaturation during drying compared with hydrogen and ionic bonding, which rarely contribute any effect [38].…”
Section: Controlling the Quality Of Dried Food Productsmentioning
confidence: 99%
“…The retention of the nutritional value of food products is dependent mainly on the freshness of the raw material and optimal control of associated drying conditions [37]. The heat effects involve in drying affect the protein components in foods especially the thiosulphide groups [38]. Its causes changes in the solubility of proteins, hydrophobic bond break has been attributed greatly to denaturation during drying compared with hydrogen and ionic bonding, which rarely contribute any effect [38].…”
Section: Controlling the Quality Of Dried Food Productsmentioning
confidence: 99%
“…This parameter is a measure of nitrogen degradation during storage and protein breakdown in raw fish (Borquez & Speek 1994; Borquez et al . 1994; Raghunath et al . 1995) and is used to determine the quality (freshness) of the raw fish, previous to its entry into the fishmeal factory.…”
Section: Resultsmentioning
confidence: 99%
“…An acceptable calibration for TVN was observed. This parameter is a measure of nitrogen degradation during storage and protein breakdown in raw ®sh (Borquez & Speek 1994;Raghunath et al 1995) and is used to determine the quality (freshness) of the raw ®sh, previous to its entry into the ®shmeal factory. The results found in this work showed that NIRS could be used to assess this parameter under industrial conditions satisfactorily.…”
Section: Nirs Calibration Statistics For Raw Minced Fishmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of same oil repeatedly for frying led to marginal but insignificant decrease in digestibility (Table 3). Heating of fish whether by cooking or drying brings about decreases in in-vitro digestibility [14,15], owing to denaturation of proteins. Thus, heating of fish during frying as well as its interaction with the frying oil would be expected to decrease its digestibility as observed here.…”
Section: Resultsmentioning
confidence: 99%